Academic Resilience and Achievement Motivation in Students Who Experience Academic Stress - Muhammad Nafitianto; Edy Purwanto (Universitas Negeri Semarang, 2024)
Students during lectures cannot be denied having academic demands and pressures. Kholidan & Alsa (2012) that the pressures and demands of lectures as a cause of stress or a source of student stressors. Another opinion states that one source of stress for students is the ambition to achieve and complete various academic tasks (Greenberg, 2004). The phenomenon of achievement motivation is often found among students, even though students need to maintain their level of academic motivation. Achievement motivation has an important role in achieving one's achievements. Achievement motivation is very important for individuals to be able to follow the learning process well (Nurazmi & Kurniawan, 2016). Resilience acts as a factor that influences achievement motivation (Mardiana et al., 2017). According to Connor & Davidson, students need certain abilities, one of which is resilience, an ability a person has to survive, overcome, and thrive in adversity (Yuliasih & Akmal, 2017). Students who have academic resilience are not easy to despair when experiencing academic difficulties. (Harahap et al., 2020). This quantitative research involved 201 UNNES Psychology students as samples taken using purposive sampling technique. The data of this study were obtained using the academic resilience scale (ARS-30) adapted by Kumalasari (2020), Motivated Strategies for Learning Questionaire Manual (MSLQM) adapted by Purwanto 2014, and Student-Life Stess Inventory (SLSI) adapted by Putra (2018). The results of the analysis obtained F of 86.218 with a significance level of 0.000 (p < 0.05), so that the hypothesis that reads